The Effect of Achievement Motivation, Competence and Self-Efficacy in Entrepreneurship on the Visionary Capabilities of Entrepreneurs, in South Kalimantan-Indonesia - Suyanto Suyanto; Endang Larasati; Indi Djastuti; Widiartanto Widiartanto; Yuwanto Yuwanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Entrepreneurial Visinoary Capability is the ability of entrepreneurs to take a mental journey from the known to the unknown, able to present a future based on facts, figures, hopes, dreams, dangers and opportunities by applying it to activities and programs until reach the aim of company wants to achieve. Identify and exploit entrepreneurial visionary capability using achievement motivation, self-efficacy and competence. Those three measures whether significant affect the entrepreneurial visionary capability or vice versa. The research was conducted using descriptive statistical research methods using Software SmartPLS to determine the frequency distribution of respondents' answers to the results of questionnaires distributed. The questionnaires include Achievement Motivation (X1), Entrepreneurial Competence (X2), Self-Efficacy (X3) and Entrepreneurtial Visionary Capability (Y). The indicators in this study use class interval criteria obtained from the calculation result: Using a significance level of 3% the result of this study indicate that the variable Achievement Motivation, Entrepreneurial Competence, and Self-Efficacy, have a significant effect on the Visionary Capabilities of Entrepreneurs.